"It Was Really Tough"—Exploring the Feelings of Isolation and Cultural Dissonance With Black American Males at a Predominantly White Institution. (May 2021) - Patterson, Anthony F.
Black American males and low socioeconomic status students face a gauntlet of obstacles when pursuing their college degrees. These young men do not earn degrees at the same rate as their peers. As campus engagement, recreation, and leisure play pivotal roles in students' experiences, investigating their influence relative to social integration might facilitate a better understanding of the issues they face. This study explored how Black American male undergraduates from low socioeconomic status backgrounds perceived the roles that campus engagement, recreation, and leisure played in their social integration. Bronfenbrenner's ecological model of human development guided the qualitative approach to this study. Seventeen participants were interviewed, and interwoven themes related to feelings of isolation and cultural dissonance emerged. Theorizing about the complex roles leisure plays, in some cases, creating isolation and cultural dissonance and, in others, helping students navigate the challenges of college are presented.